Cell Cycle Elongation Impairs Proliferation of Cerebellar Granule Cell Precursors in the Ts65Dn Mouse, an Animal Model for Down Syndrome - Contestabile, Andrea (Brain Pathol, 2008)
Mental retardation, the hallmark of Down syndrome (DS), has been attributed to the reduced number of neurons populating the DS brain. The Ts65Dn mouse model of DS displays several anomalies analogous to those in individuals with DS, including neurogenesis impairment. The goal of the current study was to determine whether cell cycle alterations underlie neurogenesis impairment in the cerebellum of the Ts65Dn mouse and to identify the molecular mechanisms responsible for this defect. In neonatal (2‐day old) Ts65Dn mice, cerebellar granule cell precursors exhibited a reduced proliferation rate (−40%) and a notable elongation (+45%) of the cell cycle. Alteration of cell cycle rate was due to elongation of the G(2) and G(1) phases. Microarray screening of cell cycle regulatory genes showed that Ts65Dn mice had a decreased expression of Cyclin B1 and Skp2, two key regulators of G(2)/M and G(1)/S transition. Results point at cell cycle elongation as major determinant of neurogenesis reduction in the cerebellum of Ts65Dn mice and suggest that this defect is specifically linked to an altered expression of two cell‐cycle regulatory genes, Cyclin B1 and Skp2. These findings may establish the basis for a therapeutic approach aimed at restoring neurogenesis in the DS brain.